ANTIOXIDANT ACTIVITY AND TOXICITY OF PUSPA (SCHIMA WALLICHII) LEAVES EXTRACT FROM INDONESIA - Widiyarti, Galuh; Supiani, Supiani; Tiara, Yova (Journal of Tropical Life Science, 2018)
Antioxidant and toxicity of Puspa (Schima wallichii) were studied. The plant extracts were prepared for bio-logical screening. Antioxidant activity of extracts was analysed by 1,1-diphenyl-2-picrylhydrazyl (DPPH) as stable free radical, while toxicity of extracts was analysed by Brine Shrimp Lethality Test (BSLT) method. The result showed that ethyl acetate, methanol and butanol extracts were very active as antioxidant, as indicated by IC50 value of 11.44, 17.97 and 12.55 µg/mL for DPPH inhibition, respectively. Whilst n-hexane extract was not active as antioxidant indicated by IC50 value of 257.91 µg/mL, but aquadest extract was less active as antioxi-dant indicated by IC50 value of 171.94 µg/mL. The toxicity test result showed that all extracts were active against Artemia salina Leach with LC50 value of 107.35 ? 902 µg/mL. Furthermore, isolation of individual bio-active compound of ethyl acetate extract that most active as antioxidant was carried out using column chroma-tography followed by preparative Thin Layer Chromatography (TLC). The active isolate was then identified using TLC, Fourier Transform Infra-Red (FTIR) and Liquid Chromatography Mass Spectroscopy (LCMS).. The identification result showed that the major compound contained a putative compound known as theanine with MS 174.26 g/mol. The isolate was very active as antioxidant with IC50 value of 48.04 µg/mL, although it was less active than the extract. The isolate was also toxic with LC50 value of 27.71 µg/mL so that puspa leaf potentially to be developed as a natural antioxidant and anticancer agent for preventing of human diseases.